Impaired Mitochondrial Bioenergetics Function in Pediatric Chronic Overlapping Pain Conditions with Functional Gastrointestinal Disorders. (14th August 2021) - Chelimsky, Gisela; Simpson, Pippa; Zhang, Liyun; Bierer, Doug; Komas, Steve; Kalyanaraman, Balaraman; Chelimsky, Thomas
Abstract : Background . Fatigue is often the primary complaint of children with functional gastrointestinal disorders (FGDI) and other chronic overlapping pain disorders (COPC). The basis for this symptom remains unknown. We evaluated mitochondrial function in the white blood cells of these patients. Methods . This prospective Children's Wisconsin IRB approved study recruited subjects aging 10–18 years from pediatric neurogastroenterology clinics and healthy comparison subjects (HC). Environmental and oxidative stressors can damage the mitochondrial respiratory chain. The known low-grade inflammation in COPC could, therefore, impact the respiratory chain and theoretically account for the disabling fatigue so often voiced by patients. Mitochondrial energy generation can be easily measured in peripheral mononuclear cells (PMC) as a general marker by the Seahorse XF96 Extracellular Flux Analyzer. We measured 5 parameters of oxygen consumption using this methodology: basal respiration (BR), ATP linked oxygen consumption (ATP-LC), maximal oxygen consumption rate (max R), spare respiratory capacity (SRC), and extracellular acidification rate (ECAR), which reflect non-electron chain energy generation through glycolysis. In health, we expect high ATP linked respiration, high reserve capacity, low proton leak, and low non-mitochondrial respiration. In disease, the proton leak typically increases, ATP demand increases, and there is decreased reserve capacity with increased non-mitochondrial respiration. Findings and clinical data were compared to healthy control subjects using a Mann–Whitney test for skewed variables, Fisher's exact test for dichotomous variables, and regression tree for association with functional outcome (functional disability inventory, FDI). Results . 19 HC and 31 COPC showed no statistically significant difference in age. FGID, orthostatic intolerance, migraine, sleep disturbance, and chronic fatigue were present in the majority of COPC subjects. BR, ECAR, and ATP-LC rates were lower in the COPC group. The low BR and ATP-LC suggest that mitochondria are stressed with decreased ability to produce ATP. Tree analysis selected SRC as the best predictor of functional disability: patients with SRC >150 had a greater FDI (more disability) compared to patients with SRC <=150, p -value = 0.021. Conclusion . Subjects with COPC have reduced mitochondrial capacity to produce ATP. Predisposing genetic factors or reversible acquired changes may be responsible. A higher SRC best predicts disability. Since a higher SRC is typically associated with more mitochondrial reserve, the SRC may indicate an underutilized available energy supply related to inactivity, or a "brake" on mitochondrial function. Prospective longitudinal studies can likely discern whether these findings represent deconditioning, true mitochondrial dysfunction, or both.